The influential Christian: learning to lead from the heart - Andrews, Michael W. (Rowman & Littlefield, 2021)
"The Influential Christian reveals how spiritual practices that exercise empathy allow Christians to cultivate influence in their personal, professional, and spiritual lives.. This process builds connection and influence. Drawing upon real-life examples, the nature of influence aligns with the significance of developing identity and integrity"--